2015
DOI: 10.1159/000434718
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins in Neonates with Rhesus Hemolytic Disease of the Fetus and Newborn: Long-Term Outcome in a Randomized Trial

Abstract: Objective: Prophylactic intravenous immunoglobulin (IVIg) does neither reduce the need for exchange transfusion nor the rates of other adverse neonatal outcomes in neonates with rhesus hemolytic disease of the fetus and newborn (rhesus HDFN) according to our randomized controlled trial analysis. Our objective was to assess the long-term neurodevelopmental outcome in the children included in the trial and treated with either IVIg or placebo. Methods: All families of the children included in the trial were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In a follow-up study of a randomized controlled trial conducted at our center, we found that the neurodevelopmental outcome in children treated with intravenous immunoglobulins for HDFN was not different from children treated with placebo [32,99]. At a median age of 4 years, NDI was detected in 3% in both the IVIG (1/34) and placebo (1/32) group.…”
Section: Long-term Outcome After Immunoglobulinsmentioning
confidence: 82%
“…In a follow-up study of a randomized controlled trial conducted at our center, we found that the neurodevelopmental outcome in children treated with intravenous immunoglobulins for HDFN was not different from children treated with placebo [32,99]. At a median age of 4 years, NDI was detected in 3% in both the IVIG (1/34) and placebo (1/32) group.…”
Section: Long-term Outcome After Immunoglobulinsmentioning
confidence: 82%
“…Lastly, developmental outcomes of children treated with IUTs that were included in a randomized controlled trial to evaluate the effectiveness of IVIG to prevent exchange transfusions were assessed. No difference in the rate of neurodevelopmental adverse outcomes was found between the placebo and interventional group [102].…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 79%
“…We were unable to stratify the data per alloimmunization type with the data provided in these articles. One of these studies represented the only prospective study with long-term outcomes [ 89 ], thereby also indicating the lack of data on long-term outcomes and the need for further research on the topic.…”
Section: Discussionmentioning
confidence: 99%